Limits of Doctors’ Criminal Liability for Patient Death under the Criminal Code and Health Law Number 17 of 2023 - Rino Rachmatullah; Ahmad Jamaludin (LifeSciFi, 2026)
Patient deaths from medical interventions have become a key issue amid rising criminal malpractice cases against doctors in Indonesia. Article 474 of the Criminal Code stipulating a prison sentence of up to five years for those who cause death through error is often applied rigidly to medical personnel without considering the complexity of the medical profession. On the other hand, Law Number 17 of 2023 concerning Health limits doctors’ criminal liability only to gross negligence (culpa lata), creating normative tension with the general provisions of the Criminal Code. This study aims to analyze the boundaries of criminal elements and regulatory harmonization in patient death cases. The research method used is normative juridical with an empirical approach, through the study of legislation and analysis of court decisions and related secondary data. The results show that there are unclear criminal boundaries due to a lack of harmonization between the Criminal Code and the Health Law, as well as the subjective application of negligence by judges. These findings indicate a risk of overcriminalization that impacts medical practice. This study concludes that there is an urgent need for clear regulatory harmonization and increased capacity of judges in understanding medical professional standards to ensure legal certainty.